2009
DOI: 10.3892/or_00000481
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5-FU/LV plus CPT-11 as first-line adjuvant chemotherapy for stage IIIa colorectal cancer

Abstract: Abstract. The aim of this study was to retrospectively evaluate the effect of adding CPT-11 to postoperative chemotherapy for stage III colorectal cancer. The subjects were 94 patients, including 60 in stage IIIa (≤3 positive nodes) and 34 in stage IIIb (≥4 positive nodes), who underwent curative resection. The clinical outcome was compared between patients receiving 5-FU/LV plus CPT-11 (FLC group) and patients receiving 5-FU/LV alone (FL group). The FLC group (54 patients) had a 3-year relapse-free survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…At least 12 lymph nodes were collected from patients in the two groups following D2 or D3 resection according to the Japanese classification (28)(29)(30). The postoperative adjuvant chemotherapy regimens were as follows: No chemotherapy in stage I, only oral anticancer agents (UFT/PSK) in stage II, and modified 5-fluorouracil (5-FU)/leucovorin (LV) or modified FOLFIRI (5-FU/LV+CPT-11) for ≥6 months in stage III (25,(31)(32)(33)(34)(35)(36). To detect metastasis/recurrence, ultrasound scan (US) and computed tomography (CT) were performed 3-4 times annually, and patients in whom US and CT simultaneously identified metastatic/recurrent disease were classified as positive for metastasis/recurrence (25,31-36).…”
Section: Introductionmentioning
confidence: 99%
“…At least 12 lymph nodes were collected from patients in the two groups following D2 or D3 resection according to the Japanese classification (28)(29)(30). The postoperative adjuvant chemotherapy regimens were as follows: No chemotherapy in stage I, only oral anticancer agents (UFT/PSK) in stage II, and modified 5-fluorouracil (5-FU)/leucovorin (LV) or modified FOLFIRI (5-FU/LV+CPT-11) for ≥6 months in stage III (25,(31)(32)(33)(34)(35)(36). To detect metastasis/recurrence, ultrasound scan (US) and computed tomography (CT) were performed 3-4 times annually, and patients in whom US and CT simultaneously identified metastatic/recurrent disease were classified as positive for metastasis/recurrence (25,31-36).…”
Section: Introductionmentioning
confidence: 99%
“…In patients who were not indicated for surgery, anticancer agents other than those mentioned above were administered as second-line treatment. Radiotherapy was added in the case of rectal cancer for the local recurrence involving the pelvic floor (12)(13)(14). As a general rule, outpatient follow-up included measurement of tumor markers 3-4 times per year and ultrasonography/computed tomography (US/CT) 3-4 times a year, with recurrence/metastasis being confirmed by both US and CT (10,13).…”
Section: Methodsmentioning
confidence: 99%
“…In general, Stage II patients received postoperative adjuvant chemotherapy with oral UFT/PSK (Krestin) for 12 months or longer (8)(9)(10). Stage III patients received intravenous 5FU/LV or 5FU/LV in combination with CPT-11 for 6 months after surgery, and then received oral UFT/Uzel (an oral calcium folinate) or UFT/PSK for 12 months or longer (11)(12)(13). In principle, surgical resection was chosen as the first-line treatment for postoperative recurrence/metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…It was considered to be the result of persistent tumor immunity leading to eradication of single cells. Also, the number of clusters is presumed to be increased compared with that in patients who have stage II/N0-localized tumors, and more potent postoperative adjuvant chemotherapy would be required for stage III patients with a high risk of recurrence (31,32). Aside from various factors such as the host immunity and tumor susceptibility to anticancer agents, the results of this study suggested that the presence of single cells + clusters of ONCs was related to a high risk of recurrence based on its high sensitivity, while ONCs are a useful negative indicator for identifying the low-risk group because the absence of ONCs showed a high NPV.…”
Section: -------------------------------------------------mentioning
confidence: 99%
“…We therefore investigated the presence of ONC clusters consisting of 2-20 tumor cells for which viability can be easily judged in addition to the conventional assessment of single cells. Clusters are assumed to be either spheres ≤0.2 mm in diameter or structures like a bunch of grapes, but it is not known at present whether or not there is an interstitial component connecting the individual cancer cell or whether the clusters contain cancer stem cells with resistance to chemotherapy agents that transmit important information for tumor survival (18,32). However, it was considered easier compared with single cells to judge the proliferative capacity, based on the nuclear structure, cytoplasmic morphology and staining.…”
Section: -------------------------------------------------mentioning
confidence: 99%